Features of the International Cooperation in Nuclear Power at the Present Stage - Dmitry S. Panteley (Модернизация, инновация, развитие)
Purpose: in article the author raises the aspects of the international cooperation in nuclear power. The author wants to analyse the multiplefactor analysis of the international regulation in the field of peaceful use of atomic energy and to reveal competitive advantages of the Russian Federation in this area.Methods: the methodological base of the research was made by set of general scientific methods and methods of the economic analysis. In particular, such methods of the scientific analysis were used as system approach, method of the comparative analysis, synthesis and analysis. From economic methods was used the method of the analysis of the branch competitiveness.Results: the author, raises the aspects of the international cooperation in nuclear power, comes to the conclusion that the specifics of branch cause need of comprehensive and close international interaction for prevention of distribution of dual-use technologies, for ensuring global and regional ecological and energy security, for ensuring the rights to use peaceful atom for needs of national economies and for observance of rules of the free market competition in such a complex branch of the world economy.Conclusions and Relevance: nuclear power is a high-tech and innovative branch of the Russian economy. Today it is one of the most dynamically developing in the country, and also plays a significant role in the world energy. Among the competitive advantages of the national nuclear power industry is the development of new technologies, flexible price offers in foreign markets, etc. The development of the branch and the sustainability of Russia's competitive position in this area on foreign markets require the development of new proposals for different regional markets and the implementation of planned measures to support the level of competitiveness.Сonclusions can be used as recommendations for developing programs to increase the competitiveness of the Rosatom State Corporation